1991
DOI: 10.1007/bf00228516
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative study of the pulsatile parameters of CRH-41 secretion in unanesthetized free-moving rats

Abstract: Having recently improved the sensitivity of the RIA CRH-41 measurements in perfusates from push-pull cannulas implanted in the rat median eminence, we explored quantitatively the pulsatile parameters of the CRH-41 measured with this technique at 2.5 or 5 min intervals in a series of unanesthetized male rats under basal conditions. The data were analysed by computer using 4 algorithms, i.e. Santen & Bardin, Ultra, Pulsar and Periodogram. Under a basal mean secretion rate of 15.5 pg CRH-41/15 min, the pulsatile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…For example, studies in the sheep have shown that ultradian rhythms of ACTH and CORT are maintained even after the hypothalamus has been surgically disconnected from the pituitary (Engler et al 1990), suggesting there must be a hypothalamic-independent pulse generator. Further supporting this idea is the observation that in the rat there is a mismatch between the frequency of CRH pulses (w3 pulses/h) (Ixart et al 1991) and the near-hourly frequency of ACTH and CORT oscillations (Carnes et al 1988a).…”
Section: The Origin Of Glucocorticoid Pulsatilitymentioning
confidence: 92%
See 1 more Smart Citation
“…For example, studies in the sheep have shown that ultradian rhythms of ACTH and CORT are maintained even after the hypothalamus has been surgically disconnected from the pituitary (Engler et al 1990), suggesting there must be a hypothalamic-independent pulse generator. Further supporting this idea is the observation that in the rat there is a mismatch between the frequency of CRH pulses (w3 pulses/h) (Ixart et al 1991) and the near-hourly frequency of ACTH and CORT oscillations (Carnes et al 1988a).…”
Section: The Origin Of Glucocorticoid Pulsatilitymentioning
confidence: 92%
“…Furthermore, episodic release of CRH has been shown in macaque (Mershon et al 1992), sheep (Caraty et al 1988, Engler et al 1989, and the rat (Ixart et al 1991(Ixart et al , 1994. The evidence of pulsatility of CRH led to the acceptance that the ultradian release of CORT was driven by a hypothalamic CRH pulse generator.…”
Section: The Origin Of Glucocorticoid Pulsatilitymentioning
confidence: 99%
“…Although there is some evidence for pulsatility of CRH (1,2), our recent work suggests that ACTH and CORT pulsatility is predominantly generated by a subhypothalamic oscillator within the pituitary-adrenal system (3,4). The amplitude of these pulses varies in a circadian manner with larger pulses occurring at the start of the active phase (morning in humans, evening in rodents).…”
mentioning
confidence: 98%
“…contributed equally to this work. 2 To whom correspondence should be addressed. Email: f.spiga@bristol.ac.uk.…”
mentioning
confidence: 99%
“…Indeed, there is evidence for episodic release of CRH from macaque hypothalamic explants (Mershon et al 1992) and for rapid changes in CRH in the median eminence of rats (Ixart et al 1991) and portal blood of sheep (Caraty et al 1988). There is, however, a mismatch between the higher frequency of CRH pulses than the ACTH/CORT pulses, and Engler et al (1990) also demonstrated the maintenance of ACTH and cortisol pulses in the sheep even after disconnection of the pituitary from hypothalamic portal blood.…”
Section: The Origin Of Hpa Pulsatilitymentioning
confidence: 99%